Exploring physicians' perception of diagnostic information in clinical practice - Vivienne C. Bachelet; Robin Osorio; Diego Silva-Villalobos; Camilo Urzúa-Álvarez; María S. Navarrete (Medwave, 2023)
A well-informed diagnostic process results in better health outcomes and less overdiagnosis. While there have been studies conducted to explore doctors' knowledge, attitudes, and practice regarding diagnostic test information, there are no reports from Latin America. We invited physician readers of a Latin American medical journal to answer a survey on their professional and demographic characteristics and previous exposure to diagnostic information training. Two hundred fifteen responded, of whom 88% agreed to some extent that diagnostic information is helpful for clinical practice and that more training is needed. This brief exploratory survey underscores the need for more resources to train in the diagnostic process and the utilization of diagnostic information in clinical practice. However, given the limitations of this study, more evidence is needed.